KNOWLEDGE AS A CATALYST: EMPOWERING PATIENTS THROUGH EDUCATIONAL INTERVENTIONS IN URINARY DIVERSION - Amira , Mahmoud Hassan; Mohammed , Ali Al-Farsi (Research Journal of Health, Medicine and Nursing, 2024)
Bladder cancer is a prevalent global malignancy, ranking as the 7th most common cancer in the United States and the 9th most common in the United Kingdom. It imposes significant economic burdens on healthcare systems. Although bladder cancer affects both men and women, it is more frequently diagnosed in men and stands as the seventh and eighth leading cause of cancer-related deaths in the USA and the UK, respectively. Several risk factors have been identified, including advanced age, exposure to carcinogens, cigarette smoking, and the presence of Schistosoma haematobium infection, particularly in African regions. Treatment options for bladder cancer often necessitate surgical intervention, which, in some cases, requires the diversion of the normal urinary flow. Urinary diversion is a surgical procedure that redirects the path of urine excretion, creating an alternative route. This procedure can be temporary or permanent and involves creating a stoma, typically from the ureters. Stomas are most commonly employed in older adults with conditions such as bladder cancer, congenital bladder defects, and unreparable birth defects. Traumatic injuries to the bladder can also necessitate urinary diversion. This article discusses the various aspects and implications of urinary diversion for bladder cancer patients, particularly in older individuals.